2018
DOI: 10.1109/tsg.2017.2696619
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-Based Transmission Line Parameter Estimation With Adaptive Data Selection Scheme

Abstract: Abstract-Accurate parameters of transmission lines are critical for power system operation and control decision making. Transmission line parameter estimation based on measured data is an effective way to enhance the validity of the parameters. This paper proposes a multi-point transmission line parameter estimation model with an adaptive data selection scheme based on measured data. Data selection scheme, defined with time window and number of data points, is introduced in the estimation model as additional v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 15 publications
0
28
0
12
Order By: Relevance
“…The simulation results illustrate that the proposed parameter identification and voltage profile calculation methods offer higher precisions compared to the other works in the literature [6], [7], [9], [12], [13], [33]. This efficiently transient voltage evaluating and transmission line parameter identifying method can be useful for other researches, such as power system transient stability [34], fault location, insulation coordination, and locating of surge arresters in the middle of overhead transmission lines [35].…”
Section: Voltage Profile Validationmentioning
confidence: 80%
See 1 more Smart Citation
“…The simulation results illustrate that the proposed parameter identification and voltage profile calculation methods offer higher precisions compared to the other works in the literature [6], [7], [9], [12], [13], [33]. This efficiently transient voltage evaluating and transmission line parameter identifying method can be useful for other researches, such as power system transient stability [34], fault location, insulation coordination, and locating of surge arresters in the middle of overhead transmission lines [35].…”
Section: Voltage Profile Validationmentioning
confidence: 80%
“…An orthogonal distance regression approach for solving zero sequence parameter estimation problem, discussing the different types of zero sequence network configurations is proposed in [12], considering noise in synchrophasor measurements, and the authors generalized the method of total least squares to the non-linear parameter estimation problem. An iterative technique derived from the Newton method is adopted to solve a multi-point transmission line parameter estimation model in [13]. Reference [14] outlines an approach for estimating the positive sequence line parameters in steady state conditions and describes its capability of detecting and identifying bad data of measurement errors and minimizing the impacts of them.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting (17) into (15), it can be found that, γ cal ≈ γ theo = (sL + R )sC (18) It shows that the proposed method can correctly extract the propagation constant γ theo from the measured one-end shortcircuited admittance Y short and the measured one-end opencircuited admittance Y open .…”
Section: A Parameters Identification Of Lumped-parameter Model Of Ltcmentioning
confidence: 87%
“…The propagation constant γ cal which is calculated using the proposed method in this paper can be obtained by (11), shown as, where γ theo = (sL + R )sC is the theoretical propagation constant. (15) provides the relationship between the derived propagation constant using terminal admittances and the theoretical propagation constant.…”
Section: A Parameters Identification Of Lumped-parameter Model Of Ltcmentioning
confidence: 99%
See 1 more Smart Citation